2009
DOI: 10.1093/sleep/32.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Children Show Individual Night-to-Night Variability of Periodic Limb Movements in Sleep

Abstract: In this sample of children, considerable individual night-to-night variability of PLMS indexes was observed. This finding has important clinical relevance for the diagnosis of restless legs syndrome and PLMD and may have an impact on future studies that correlate individual PLMS severity with frequently associated symptoms, such as negative affect, fatigue, and inattention. Our data, however, also suggest that individual PLMS variability is random and not likely to skew the group-level analysis of treatment ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 59 publications
2
25
1
Order By: Relevance
“…Individual night-to-night variability of PLMS in children was documented. However, Picchietti et al demonstrated that this variability is random and not likely to skew the group-level analysis [35]. Another limitation or bias to our study is the rather small power of the study group and the condition of a used alarm therapy in some children before they were consulted and participated in the study.…”
Section: Discussionmentioning
confidence: 85%
“…Individual night-to-night variability of PLMS in children was documented. However, Picchietti et al demonstrated that this variability is random and not likely to skew the group-level analysis [35]. Another limitation or bias to our study is the rather small power of the study group and the condition of a used alarm therapy in some children before they were consulted and participated in the study.…”
Section: Discussionmentioning
confidence: 85%
“…Despite concerns about dietary inadequacy and evidence that ID can affect attention, sleep, and cognitive development, [18][19][20][21][22][23][24] no studies in the United States have examined iron status or the relationship between iron intake and iron status in children with ASD. It is important to identify remediable medical risk factors for both behavioral and medical disorders in children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] Dietary inadequacy of iron does not appear to be the only risk factor for low iron stores. Future studies will need to explore the complexity of iron metabolism and include central laboratory testing, markers of inflammation such as C-reactive protein, and other markers of iron absorption.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a multisite study investigating the effects L-DOPA on in children with ADHD, baseline end point PSG was performed; the results of the study have been reported earlier [30,31]. In our paper, we have reanalyzed data from a subsample of children aged seven to 12 years recruited at the Carle Foundation Hospital/University of Illinois.…”
Section: Subjectsmentioning
confidence: 99%